2017
DOI: 10.1101/194126
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BldC delays entry into development to produce a sustained period of vegetative growth inStreptomyces venezuelae

Abstract: 14 not peer-reviewed)

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…The four direct BldD‐(c‐di‐GMP) targets ( cdgA , cdgB , cdgC , and cdgE ) are also directly controlled by the response regulator MtrA, which further binds to the promoters of cdgF and rmdB (Som et al ., 2017). Moreover, cdgB is directly repressed by the transcription factor WhiA, while cdgE is directly activated by the MerR‐like regulator BldC (Bush et al ., 2013, Bush et al ., 2019). Such multilayered transcriptional control of c‐di‐GMP synthesis and degradation suggests that levels of this molecule are fine‐tuned in response to disparate signal transduction cascades.…”
Section: Resultsmentioning
confidence: 99%
“…The four direct BldD‐(c‐di‐GMP) targets ( cdgA , cdgB , cdgC , and cdgE ) are also directly controlled by the response regulator MtrA, which further binds to the promoters of cdgF and rmdB (Som et al ., 2017). Moreover, cdgB is directly repressed by the transcription factor WhiA, while cdgE is directly activated by the MerR‐like regulator BldC (Bush et al ., 2013, Bush et al ., 2019). Such multilayered transcriptional control of c‐di‐GMP synthesis and degradation suggests that levels of this molecule are fine‐tuned in response to disparate signal transduction cascades.…”
Section: Resultsmentioning
confidence: 99%
“…Phenotypically, BldC acts to delay entry into development to produce a sustained period of vegetative growth, and so bldC mutants initiate development prematurely [27 ]. BldC binds to hundreds of promoter regions and has a global influence on the transcription profile of the cell, exerting positive effects on the activity of some of its target promoters and negative effects on others [27 ].…”
Section: Diverse Functions and Modes Of Dna Binding In The Merr Supermentioning
confidence: 99%
“…Phenotypically, BldC acts to delay entry into development to produce a sustained period of vegetative growth, and so bldC mutants initiate development prematurely [27 ]. BldC binds to hundreds of promoter regions and has a global influence on the transcription profile of the cell, exerting positive effects on the activity of some of its target promoters and negative effects on others [27 ]. Bioinformatic analysis suggested [28] and structural studies demonstrated [29 ] that BldC is related to the DNAbinding domain of MerR family transcription factors like MtaN ( Figure 1) [30], consistent with the transcription factor-like behaviour of BldC.…”
Section: Diverse Functions and Modes Of Dna Binding In The Merr Supermentioning
confidence: 99%
See 1 more Smart Citation
“…The four direct BldD-(c-di-GMP) targets ( cdgA, cdgB, cdgC and cdgE ) are also directly controlled by the response regulator MtrA, which further binds to the promoters of cdgF and rmdB (24). Moreover, cdgB is directly repressed by the transcription factor WhiA, while cdgE is directly activated by the MerR-like regulator BldC (41, 42). Such multi-layered transcriptional control of c-di-GMP synthesis and degradation suggests that levels of this molecule are fine-tuned in response to disparate signal transduction cascades.…”
Section: Resultsmentioning
confidence: 99%